A novel series of oligomers from 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans stereochemistry - Edwards, A; Sanjayan, G; Hachisu, S; Tranter, G; Fleet, G (2006)
Two tetrahydrofuran-based γ-amino acids [2,4-cis and 2,4-trans] were subjected to iterative peptide-coupling procedures to afford dimeric, tetrameric and hexameric carbopeptoids in good yield. These homooligomers were prepared for secondary structural study-to ascertain the conformational preference inherent in the monomer units. The l-xylo oligomers were protected with triethylsilyl ethers to increase the range of solvents suitable for structural investigation. Initial secondary structure data indicate the presence of hydrogen-bonded conformations in the l-ribo series. © 2006 Elsevier Ltd. All rights reserved.